Detection of Metallo b-Lactamases in Clinical Isolates of Pseudomonas aeruginosa in a Tertiary Care Hospital (Sir Salimullah Medical College Journal, 2022)
Background: Pseudomonas aeruginosa are among the major nosocomial pathogens that demonstrate all known enzymatic and mutational mechanism of bacterial resistance. They are able to acquire drug resistant determinants by horizontal transfer of mobile genetic elements coding for class B carbapenemases, called metallo b lactamases which hydrolyze all b lactams except aztreonam. MBLs like bla VIM has been reported among isolates of Enterobacteriaceae family, P.aeruginosa and other gram negative nonfermenters. On the other hand NDM-1 was first identified in Klebsiella Pneumoniae. Its spread among Pseudomonaceae implies possibility of numerous New NDM-1 cases to be detected in near future.Objective: The study aimed to isolate VIM and NDM-1 producing P. aeruginosa from burn wound and to see their susceptibility pattern.Materials and methods: P. aeruginosa was isolated by culturing on Macconkey agar media both on 370 C and 420 C and biochemical test. For gene detection organisms were stored at -700C, bla VIM and bla NDM-1 was detected by PCR. Susceptibility pattern of organisms were done by Kirby Bauer Disc Diffusion Method.Result: Among the 98 isolated P. aeruginosa 21(47.7%) were VIM producers and 6 (13.6%) NDM-1 producers. VIM producers were 80.9% resistant to imipenem and NDM-1 producers were 100% resistant imipenem.Discussion: VIM producing P. aeruginosa was isolated from burn patient in accordance with other study, NDM-1 producing P. aeruginosa is emerging that are more resistant to conventional antibiotcs even to the last resort drug imipenem.Conclusion: Imipenem resistence is increasing among P. aeruginosa as a result of acquiring MBL genes. Risk factors for acquiring resistance is increased carbapenem use, longer hospital stay, ICU admission, being on total parenteral nutrition, using catheter and tubes. In this study patient in whom imipenem resistant isolates were identified had hospital stay more than 7 daysSir Salimullah Med Coll J 2022; 30: 35-39